BOOK REVIEW Digital homiletics: The theology and practice of online preaching - J. Hurter (Acta Theologica)
A book review of "Digital homiletics: The theology and practice of online preaching " by Yang, Sanggu A. (2024) Fortress Press: Minneapolis. 173 pages.